2016
DOI: 10.1039/c5dt03402g
|View full text |Cite
|
Sign up to set email alerts
|

N-Nitrosamine-{cis-Re[CO]2}2+ cobalamin conjugates as mixed CO/NO-releasing molecules

Abstract: Mixed CO/NO-releasing molecules were prepared by conjugation of the 17-electron rhenium dicarbonyl cis-[Re(CO)2Br4](2-) complex to N-nitrosamine modified cyanocobalamin (B12) bio-vectors. The species were fully characterized by standard analytical techniques, including X-ray crystallography for cyanocobalamin-5'-O-pyrazine and () and its N-pyrazine nitrosylated derivative (). The N-nitrosamine B12 derivatives are able to liberate low NO doses in buffer solutions and appear to be "activated" towards NO release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…It is unclear to us at the present stage why or how the ethynyl-α-diimine ligands influence the anticancer activity of the molecules and render the CO-depleted metal fragments of Mn-2 and B 12 -Mn-2 active. We have previously shown that, e.g., NO release of organic N-nitrosamine is activated if the molecules are in contact with cultured cells [53]. Here perhaps a similar slow activation is at play for these photoCORMs.…”
Section: Discussionmentioning
confidence: 88%
“…It is unclear to us at the present stage why or how the ethynyl-α-diimine ligands influence the anticancer activity of the molecules and render the CO-depleted metal fragments of Mn-2 and B 12 -Mn-2 active. We have previously shown that, e.g., NO release of organic N-nitrosamine is activated if the molecules are in contact with cultured cells [53]. Here perhaps a similar slow activation is at play for these photoCORMs.…”
Section: Discussionmentioning
confidence: 88%
“…Zobi and coworkers used (CN)Cbl as a scaffold for carbon monoxide CO‐releasing complexes ,,. By functionalizing cobalamin both at the ribose and at β‐axial position they obtained mixed CO/NO‐releasing molecules (Scheme ) . To this end, cobalamin was firstly functionalized at the R 5′ ‐OH group with a macrocyclic amine (compounds 45 a – c ) and subsequently treated with NaNO 2 (compounds 46 a – c ).…”
Section: Double‐conjugated Cobalaminsmentioning
confidence: 99%
“…To this end, cobalamin was firstly functionalized at the R 5′ ‐OH group with a macrocyclic amine (compounds 45 a – c ) and subsequently treated with NaNO 2 (compounds 46 a – c ). The resulting N ‐nitrosamine cobalamins 46 a – c were reacted with [Et 4 N] 2 [Re II (CO) 2 Br 4 ] furnishing derivatives 47 a – c which were found to liberate CO and small doses of NO in buffer solutions and exhibited cytoprotection in an ischemia‐reperfusion model …”
Section: Double‐conjugated Cobalaminsmentioning
confidence: 99%
“…Recent research efforts by other groups towards developing water-soluble photoCORMs have employed different appendages to the car-bonyl complexes to improve their solubility. For example, Schatzschneider and co-workers have reported a peptide appended photoCORM, 41 while Zobi and co-workers have attached photoCORMs to vitamin B 12 platform 42,43 to achieve solubility in aqueous media. In this report, complex 2 represents a new class of highly water-soluble photoCORM with a much simpler design and straightforward synthetic strategy.…”
Section: Resultsmentioning
confidence: 99%